2007
DOI: 10.2141/jpsa.44.389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Acid Salt on the Performance and Gut Health of Broiler Chicken

Abstract: An experiment was conducted to determine the influence of organic acid salt supplementation on the performance and gut health of broiler chickens. One hundred and twenty day old commercial Vencobb-+** broiler chicks were randomly distributed into three groups having four replicates of +* birds in each group. Control (C) birds were o#ered standard basal diet and treatment + and , (T+ and T,) were having diets with ammonium formate or calcium propionate (-gm/kg diet). Organic acid salt supplementation increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 15 publications
6
90
2
11
Order By: Relevance
“…This may be the reason for the largest jejuna villi surface area (P <0.0001) that was observed in T3 and T4 birds. As reported by Paul et al (2007), the increase of villous height of various small intestine segments may be attributed to the role of the intestinal epithelium as a natural barrier to pathogenic bacteria and toxic substances that are present in the intestinal lumen. Furthermore, M. oleifera leaves contain short-chain carbohydrates, glycosides, which are reported to cause major increases in the height of the jejuna villi compared with AGP and AGP-free diets (Baurhoo et al, 2009).…”
Section: Resultsmentioning
confidence: 70%
“…This may be the reason for the largest jejuna villi surface area (P <0.0001) that was observed in T3 and T4 birds. As reported by Paul et al (2007), the increase of villous height of various small intestine segments may be attributed to the role of the intestinal epithelium as a natural barrier to pathogenic bacteria and toxic substances that are present in the intestinal lumen. Furthermore, M. oleifera leaves contain short-chain carbohydrates, glycosides, which are reported to cause major increases in the height of the jejuna villi compared with AGP and AGP-free diets (Baurhoo et al, 2009).…”
Section: Resultsmentioning
confidence: 70%
“…However, the results for dietary formates were inconsistent. Patten and Waldroup (1988) observed decreased feed efficiency by dietary supplementation of calcium formate from 7.2 to 28.9 g/kg, whereas Paul et al . (2007) reported improved body weight gain and feed efficiency with diets containing 3 g/kg ammonium formate.…”
Section: Formic Acid and Its Saltsmentioning
confidence: 85%
“…In four previous experiments (Paul et al ., 2007;Samanta et al ., 2008;Panda et al ., 2009a;Salgado-Tránsito et al ., 2011), 6 out of 10 organic acid-supplemented groups showed pH reduction in the proventriculus compared with the control groups. However, the reduction achieved statistical significance in only one experiment (Panda et al ., 2009a).…”
Section: Effects On the Ph Of The Gastrointestinal Tract (Git)mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, several studies have shown that VFAs have antibacterial activity (Dibner and Buttin, 2002;Antongiovanni et al, 2007;Paul et al, 2007;Isabel and Santos, 2009;Khodambashi et al, 2013;Milbradt et al, 2014). Unlike inorganic acids, VFAs are easily absorbed through the cell wall of bacteria and damage the structure of DNA in the cells' nuclei which lead to disrupting bacterial multiply, so cell death can accrue (Van Immerseel et al, 2006;Isabel and Santos, 2009;Milbradt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%